ON THE MECHANISM OF ACTION OF CRINUM MACOWANII BULB EXTRACT (CAEB) EFFECT ON THE HEAMODYNAMICS OF THE WISTAR RAT - Burger, A.; Persson, K.; Mugabo, P.; Green, I. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Crinum macowanii is used in traditional medicine. The mechanism of action has to be investigated to improve efficacy and safety. The effects of the CAEB (0.05 to 3 mg/kg, i.p.) on the haemodynamics (HR, Psys, and Pdiast) of anaesthetized normotensive Wistar rats as well as the general method are reported on separately. The toxic dose (80%) as determined from dose response curves for Atropine, Atenolol, Prazosin, Reserpine and Verapamil was administered in combination with CAEB to elucidate the mechanism of action in the in vivo anaesthetized normotensive rat model. Atropine (1.2 mg/kg i.v.), Atenolol (6.0 mg/kg i.v.), Prazosin (400 ug/kg i.v.), and Reserpine (0.6 mg/kg i.v.) in combination with CAEB did not significantly (P>0.01) affect any of the measured parameters when compared to CAEB on its own. The inability of these drugs (shown in brackets below) to alter the response to CAEB at the above doses indicate that CAEB does not exert its effects through muscarinic receptors (Atropine), adrenoceptors (Atenolol), 1-adrenergic receptors (Prazosin) or the postganglionic sympathetic nerve terminals (Reserpine). When rats were pre-treated with the Ca-channel blocker Verapamil (4,8 mg/kg) significant (P<0.01) differences in the HR, Psys and Pdiast were observed when compared to CAEB on its own. It could be interpreted that the Ca-channels are involved in the cardiovascular effect of CAEB, or that Verapamil caused a general decrease in the paramaters (analagous to a baseline shift). Correcting for this baseline shift indicates that the CAEB effect is not mediated by a mechanism involving Ca-channels.